Does childcare influence socioeconomic inequalities in unintentional injury? Findings from the UK Millennium Cohort Study. Issue 2 (24th November 2009) - Pearce, A; Li, L; Abbas, J; Ferguson, B; Graham, H; Law, C; ,
Abstract : Background: In recent decades the proportion of infants and young children being cared for in childcare has increased. Little is known about the impact that non-parental care has on childhood unintentional injury and whether this varies by socioeconomic group. Methods: Using data from a contemporary UK cohort of children at age 9 months (N = 18 114) and 3 years (N = 13 718), Poisson regression was used to explore the association between childcare type (parental, informal, formal) and the risk of unintentional injury, overall and by socioeconomic group. Results: At age 9 months there was no overall association between childcare and injury. However, when stratifying the analyses, infants from higher socioeconomic groups were less likely to be injured if they were cared for in formal childcare (compared with being cared for only by a parent), whereas those from lower social groups were more likely to be injured. At age 3 years informal childcare was associated with an increased risk of injury overall; in the stratified analyses this increased risk occurred only in less affluent groups. Formal childcare was no longer associated with injury at age 3 in any strata. Conclusions: Previous findings have shown that childcare can have a positive influence on childhood injury; however, a recent Unicef report highlighted that a lack of access to high-quality childcare could lead to a widening of inequalities. Our analyses indicate that childcare does have the potential to widen inequalities in injury; further research is required to understand why childcare has a differential impact on unintentional injury and how this might be prevented.